IBC-Ox22 Greater Adherence to Mediterranean Diet leads to longer term weight loss. (30th November 2022) - Simpson, T; Billy, H
Abstract:  : We were able to obtain dietary data of 134 weight loss surgery patients with an average follow up of five years with annual scoring of the 9 point Mediterranean Diet. The closer adherence to the MD showed more weight loss than those who had not. Background: The Mediterranean Diet has been associated with decreased all cause mortality for those who adhere strongly to it, as well as decreased risk of heart disease, and cancer. The diet is rich in polyphenols with fruits, vegetables, legumes, fish, mono-unsaturated fats, whole grains, while minimizing dairy, meat and poultry, and some moderate alcohol consumption. Methods: Pre operatively all bariatric patients patients were counseled about the Mediterranean diet, how to score the diet, and adherence to the diet was reemphasized at their follow ups. Annually they were asked to fill out their scores. We looked at other diet plans that some of the patients reported (low carbohydrate, weight watchers) and the results were not significant. Results: Of the 134 patients there were 65 which had scores of 5 points or more and showed an absolute reduction in weight of 54% total weight loss on average, vs those of 1-3 who had 32% total weight loss (total of 60 patients). The remaining 9 patients who escorted 4 points had a wide spread of weight loss that could not be calculated (these patients predominantly followed a self-described low-carbohydrate diet). There was no difference in weight loss regarding the type of surgery that the patient had (Lap-Band (N=74) vs Gastric Sleeve (N=50) vs Gastric bypass (N=10). Nor was there any difference in weight loss when measuring physical activity. Using the 9 point scale of the Mediterranean Diet those who had greater than 5 of the 9 points on the MD had greater weight loss over five years than those who were 0-3. Those who scored 4 points were indeterminate. Conclusions: The Mediterranean Diet scale provides a quick and easy guide, providing targets for patients (example, less than 4 ounces per day of poultry or meat is a point, more is 0 points). The emphasis on a post operative diet for health, as opposed to weight loss, inadvertently provided a good model for post operative weight loss.